2021
DOI: 10.1007/s10548-021-00835-3
|View full text |Cite
|
Sign up to set email alerts
|

Resting‐State EEG Microstates Parallel Age‐Related Differences in Allocentric Spatial Working Memory Performance

Abstract: Alterations of resting-state EEG microstates have been associated with various neurological disorders and behavioral states. Interestingly, age-related differences in EEG microstate organization have also been reported, and it has been suggested that resting-state EEG activity may predict cognitive capacities in healthy individuals across the lifespan. In this exploratory study, we performed a microstate analysis of resting-state brain activity and tested allocentric spatial working memory performance in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 94 publications
(183 reference statements)
2
20
0
Order By: Relevance
“…Four microstate topographies with right frontal to left posterior, left frontal to right posterior, frontal to occipital and fronto-central configurations matched the most frequently reported microstate classes in the literature and were labeled as microstates A, B, C and D, respectively [44]. Among three additional topographies, one had left lateralized activity and was similar to microstate E reported in studies by [21,22,45] and was labeled accordingly as microstate E. One topography displayed posterior activity and matched microstate F reported in studies by [21,22,46], microstate E reported in studies by [47][48][49] and microstate C reported in study [50] and was further labeled as microstate F. The remaining topography had right lateralized activity and was similar to microstate G from study by [22] and microstate F reported in studies by [45,49]; this was further labeled as microstate G (Figure 1C). The extracted seven microstates explained 83.8% of the global variance.…”
Section: Eeg Microstatesmentioning
confidence: 63%
“…Four microstate topographies with right frontal to left posterior, left frontal to right posterior, frontal to occipital and fronto-central configurations matched the most frequently reported microstate classes in the literature and were labeled as microstates A, B, C and D, respectively [44]. Among three additional topographies, one had left lateralized activity and was similar to microstate E reported in studies by [21,22,45] and was labeled accordingly as microstate E. One topography displayed posterior activity and matched microstate F reported in studies by [21,22,46], microstate E reported in studies by [47][48][49] and microstate C reported in study [50] and was further labeled as microstate F. The remaining topography had right lateralized activity and was similar to microstate G from study by [22] and microstate F reported in studies by [45,49]; this was further labeled as microstate G (Figure 1C). The extracted seven microstates explained 83.8% of the global variance.…”
Section: Eeg Microstatesmentioning
confidence: 63%
“…However, the study shows Map C, which is not reflected in our study. [24] Thus, simultaneous visual and autonomic processing with attentional relocation and salience network could be the resting networks activated in these microstates.…”
Section: Discussionmentioning
confidence: 95%
“…Also, they represent the basic building blocks of the chain of spontaneous conscious mental processes, and that their occurrence and temporal dynamics determine the quality of mentation [3]. In addition, these EEG microstates could be age-dependent, and may predict cognitive capacities in healthy individuals across the lifespan [4]. These states could have different applications so.…”
mentioning
confidence: 99%
“…Figure2. Topographic EEG images for different brain waves during dream[1][2][3][4][5][6][7][8][9][10][11][12][13][14] …”
mentioning
confidence: 99%